Economic Growth and Intra-Industry Trade - Leitão, Nuno Carlos (Asian Journal of Empirical Research, 2012)
The purpose of this article is to investigate the impact of marginal intra-industry trade on economic growth. The results indicate that economic growth is a dynamic process. The change of intra-industry has a positive impact on economic growth. This paper confirms relevant theoretical hypothesis as foreign direct investment and globalization promote the economic growth.